Development and Testing of an Electronic Multidisciplinary Rounding Tool. (2019) - Gunter, Elizabeth P.; Viswanathan, Meera; Stutzman, Sonja E.; Olson, DaiWai M.; Aiyagari, Venkatesh
Abstract : ABSTRACT : Patients hospitalized with neurologic and medical issues in the neuroscience critical care unit have widely varying and complex disease states that can change rapidly. The large amount of data that must be reviewed regularly by medical staff members presents a challenge to the provision of high‐quality care to these patients. In an effort to lessen the burden, the authors' team implemented an electronic multidisciplinary rounding tool, which facilitates team communication by allowing accurate and concise review of patient information. The rounding tool is part of an ongoing quality improvement project and has been in use for 4 years. Nurses have reported that the tool provides a comprehensive summary of the patient's hospital stay that facilitates handoff during shift changes. A survey of nursing staff members demonstrated high levels of satisfaction with the tool during both multidisciplinary rounds and handoffs.